Following the Death of Ms A: A Local Authority Response to Transitional Safeguarding. Issue 1 (1st January 2022) - Wallace, Martin; Cocker, Christine
Abstract : This article discusses work done over several years in the London Borough of Havering (LBH) to develop and strengthen services for young people transitioning from Children's Services to adulthood, care-experienced young people in particular. The impetus for this development work was a Safeguarding Adult Review (SAR) published in 2017 concerning a care-experienced young adult, Ms A, who was receiving Leaving Care services at the time of her death at the age of 20. Following a successful funding bid to the Department for Education, LBH made significant investment in transitions services, co-producing these with young adults themselves in conjunction with a work-support mental health charity MAC-UK. This work resulted in the creation of: The Cocoon, a new 'one-stop shop' onsite multi-agency service provision; and the Transitions Panel, a new multi-agency planning forum. This article describes the development of The Cocoon and the Transitions Panel, and summarises the impact of these developments.